Immunohistochemical analysis of retinoblastoma cell phenotype using neuronal and glial cell markers - Orellana,María Eugenia (2016)
ABSTRACT Purpose: The cellular origin of retinoblastoma is uncertain as constituent tumor cells heterogeneously express markers of both immature and mature retinal cells. An immunohistochemical analysis of cellular origin may yield valuable insights into disease progression and treatment options. This study aimed to determine the cellular origin of retinoblastoma in a large case series and correlate these findings with histopathological prognostic factors. Methods: Thirty-nine retinoblastoma cases were histopathologically diagnosed and analyzed by immunohistochemistry using monoclonal antibodies against the immature neural cell marker SRY-box containing gene 2 (SOX-2), the mature neuronal cell marker microtubule-associated protein 2 (MAP2), and the mature glial cell marker glial fibrillary acidic protein (GFAP). Histopathological features were also evaluated, including patterns of growth, differentiation, vitreous seeding, and choroidal/scleral, optic nerve, and anterior chamber invasion. Two retinoblastoma cell lines, WERI-1 and Y79, were studied by immunocytochemistry using the same antibodies. Results: Expression of SOX-2 was strong in 97.4% of retinoblastoma cases, while MAP-2 was expressed in 59% of cases. Immunostaining for GFAP was positive only in reactive stromal astrocytes interspersed amongst tumor cells and in peritumoral tissue. There was no correlation between histopathological prognostic factors and immunohistochemical markers. Retinoblastoma cell lines showed strong positivity for SOX2 (90% of WERI-1 cells and 70% of Y79 cells) and MAP2 (90% of cells in both lines). GFAP was completely negative in both cell lines. Conclusion: The majority of retinoblastomas and both RB cell lines expressed an immature neural and/or a mature neuronal cell marker, but not a glial marker. These results indicate a typical neuroblast or neuronal origin and eliminate astrocyte differentiation from neural stem cells as the source of retinoblastoma.